Security Improvement Mechanisms in Software-Defined Internet of Things - Seyedakbar Mostafavi; Hussaindad Saadat; Razieh Allamehzadeh (JOIV : International Journal on Informatics Visualization, 2020)
The IoT contains millions of heterogeneous smart objects that are connected together through the Internet platform. These heterogeneous smart objects deal with different protocols, technologies and resources, therefore each of them requires diverse security services in heterogeneous environments. Therefore, providing security services in heterogeneous environments is a daunting task for network providers that cannot be guaranteed through the traditional network architecture. Wide distribution and openness of IoT smart objects makes them very vulnerable to attacks and it can be easily targeted by cyber-attacks. Software-Defined Networking (SDN) is a new paradigm that separates the control plane from data plane t a global network view by centralized controller. Integrating the software-defined network with the Internet of Things can provide better access control and security mechanisms. Software-defined networking provides better control and management possibilities to manage and secure Internet of Things in a good manner. In this paper, we discuss about IoT architecture, security challenges in IoT, SDN architecture, security challenges in each layers of the SDN and software-defined IoT. In addition, we provide solutions to security problems in IoT through software-defined networking approach.